THE ROLE OF CRITICAL THINKING IN TEACHING READING AND WRITING - Khaydarova Nigora; Ataullayeva Madina (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation:  Critical  thinking  is  crucial  for  developing  reading  and  writing skills,  transforming  them  into  engaging  processes.  This  article  explores  how  it enhances  students'  abilities  to  analyze  and  synthesize  information,  emphasizing essential  cognitive  skills  like  inference  and  metacognition.  It  discusses  effective pedagogical strategies and argues that critical thinking is vital for academic success and informed decision-making in today’s complex information landscape.